2008
DOI: 10.1196/annals.1410.030
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Activation during Combined Mental and Physical Stress in Women Depends on Trait Anxiety and the Phase of the Menstrual Cycle

Abstract: The aim of this study was to investigate the influence of trait anxiety and menstrual cycle phase on neuroendocrine activation during combined mental and physical stress procedure in 40 healthy female subjects. Women at the upper (anxious) and lower (nonanxious) limits of the normal range of a trait anxiety scale were exposed to the stress procedure consisting of a mental component (Stroop test) and handgrip exercise. Salivary cortisol levels, cardiovascular parameters, and cognitive performance in the Stroop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…More studies are available to compare the current sample size with studies that have examined how cortisol reactivity to agentic stressors is related to sex and hormonal factors. The number of participants in this study is in line with the sample sizes observed in other agentic stressor studies examining the effects of oral contraceptive users vs. nonusers [ N = 57; Kirschbaum et al, ], follicular vs. luteal cycle phase [ N = 78 free cycling women in Lustyk et al, and N = 40 women in Hlavacova et al, ], and sex with combined hormone status [ N = 81 total males and females in the follicular phase, luteal phase, taking oral contraceptives; Kirschbaum, et al, and N = 80 total males and females in the follicular and luteal phase; Childs et al, ]. Ideally, future studies examining the effect of rejection on cortisol reactivity will incorporate large sample sizes that enable the systematic comparison of males as well as free cycling females in the luteal and follicular phases, and female oral contraceptive users.…”
Section: Discussionsupporting
confidence: 71%
“…More studies are available to compare the current sample size with studies that have examined how cortisol reactivity to agentic stressors is related to sex and hormonal factors. The number of participants in this study is in line with the sample sizes observed in other agentic stressor studies examining the effects of oral contraceptive users vs. nonusers [ N = 57; Kirschbaum et al, ], follicular vs. luteal cycle phase [ N = 78 free cycling women in Lustyk et al, and N = 40 women in Hlavacova et al, ], and sex with combined hormone status [ N = 81 total males and females in the follicular phase, luteal phase, taking oral contraceptives; Kirschbaum, et al, and N = 80 total males and females in the follicular and luteal phase; Childs et al, ]. Ideally, future studies examining the effect of rejection on cortisol reactivity will incorporate large sample sizes that enable the systematic comparison of males as well as free cycling females in the luteal and follicular phases, and female oral contraceptive users.…”
Section: Discussionsupporting
confidence: 71%
“…Comparing stress responses in men and women is complicated by variations related to menstrual cycle. Several studies have investigated responses to cognitive and stressful challenges during different phases of the menstrual cycle (Polefrone & Manuck, 1988; Stoney, Owens, Matthews, Davis, & Caggiula, 1990; Weidner & Helmig, 1990; Tersman, Collins, & Eneroth, 1991; Sita & Miller, 1996; Litschauer et al, 1998; Sato & Miyake, 2004; Carter& Lawrence, 2007; Hlavacova, Wawruch, Isonova, & Jezova, 2008), although only a few have employed the TSST or a similar speech task (Kirschbaum et al, 1995a; Kirschbaum et al, 1999; Pico‐Alfonso et al, 2007). In general, these studies suggest that cardiovascular, subjective, and cortisol responses to stress do not vary across the menstrual cycle (Kirschbaum et al, 1995a; Kirschbaum et al, 1999; Pico‐Alfonso et al, 2007), except for one study which found greater salivary cortisol responses to stress during the luteal phase (Kirschbaum et al, 1999).…”
mentioning
confidence: 99%
“…Another limitation is that we did not measure hormone levels without any manipulation in the same subjects at the same time of the day. However, according to our previous data as well as other studies, stress hormone concentrations are relatively stable during the early afternoon [13,30,31], and the reproducibility of the mental and physical stress test is good [18,23,32]. …”
Section: Discussionmentioning
confidence: 61%
“…This is not surprising as cortisol release does not exhibit changes in response to many model situations with mental challenge [16,17,18,19,20,21]. Similarly, the short handgrip exercise used [22] or combination of handgrip exercise with mental work [18,23] does not induce a profound rise in cortisol release. Cortisol is the endocrine parameter that is most frequently linked to emotional states and coping with stress [24,25].…”
Section: Discussionmentioning
confidence: 99%